Clinical outcomes of immunocompromised patients on extracorporeal membrane oxygenation support for severe acute respiratory failure. (18th October 2019) - Na, Soo Jin; Park, So Hee; Hong, Sang-Bum; Cho, Woo Hyun; Lee, Sang-Min; Cho, Young-Jae; Park, Sunghoon; Koo, So-My; Park, Seung Yong; Chang, Youjin; Kang, Byung Ju; Kim, Jung-Hyun; et al.
Abstract: : OBJECTIVES: There are limited data regarding extracorporeal membrane oxygenation (ECMO) support in immunocompromised patients, despite an increase in ECMO use in patients with respiratory failure. The aim of this study was to investigate the clinical characteristics and outcomes of immunocompromised patients requiring ECMO support for severe acute respiratory failure. METHODS: Between January 2012 and December 2015, all consecutive adult patients with severe acute respiratory failure who underwent ECMO for respiratory support at 16 tertiary or university-affiliated hospitals in South Korea were enrolled retrospectively. The patients were divided into 2 groups based on the immunocompromised status at the time of ECMO initiation. In-hospital and 6-month mortalities were compared between the 2 groups. In addition, association of immunocompromised status with 6-month mortality was evaluated with logistic regression analysis. RESULTS: Among 461 patients, 118 (25.6%) were immunocompromised. Immunocompromised patients were younger and had lower haemoglobin and platelet counts than immunocompetent patients. Ventilatory parameters and the use of adjunctive/rescue therapies were similar between the 2 groups, but prone positioning was more commonly used in immunocompetent patients. Successful weaning rates from ECMO (46.6% vs 58.9%; P = 0.021) was lower and hospital mortality (66.1% vs 59.8%; P = 0.22) was higher in immunocompromised patients. In addition, immunocompromised status was associated with higher 6-month mortality (74.6% vs 64.7%, adjusted odds ratio 2.10, 95% confidence interval 1.02–4.35; P = 0.045). CONCLUSIONS: Immunocompromised patients treated with ECMO support for severe acute respiratory failure had poorer short- and long-term prognoses than did immunocompetent patients.